2012
DOI: 10.1039/c1an15833c
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics study on Fuzi and its processed products using ultra-performance liquid-chromatography/electrospray-ionization synapt high-definition mass spectrometry coupled with pattern recognition analysis

Abstract: The lateral root of Aconitum carmichaelii Debx is named "Fuzi" which is widely distributed across Asia and North America and has been used to relieve joint pain and treat rheumatic diseases for over two thousand years. However, it has very narrow therapeutic ranges and despite the toxicological risk, its usage remains very high. A traditional Chinese processing approach (Paozhi, detoxifying measure) is necessary to remove the poisonous Aconitum alkaloids mainly deriving from the diester diterpene alkaloids (DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 31 publications
1
60
0
Order By: Relevance
“…Structural characterization and toxicities of C 19 -diterpenoid alkaloids have been widely studied, the differentiation of Aconitum species is challenging because of their similar appearance and chemical components [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Structural characterization and toxicities of C 19 -diterpenoid alkaloids have been widely studied, the differentiation of Aconitum species is challenging because of their similar appearance and chemical components [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Raphides was the common toxic substance of Araceae toxic TCM with lectin protein, which could produce acute excitant inflammation toxicity (Sun et al 2012). This study showed that the raphides excitant and lectin proflammatory were significantly decreased during processing with alum, further demonstrating that processing with alum decreased the toxicity of Araceae TCM.…”
Section: Discussionmentioning
confidence: 88%
“…[1112] A proper pharmaceutical processing methodology may significantly alter the pharmacological properties of the original crude TCM, such as the reduction of toxicity and the enhancement of pharmaceutical efficacy. [1314]…”
Section: Introductionmentioning
confidence: 99%